(untitled) (The Pretoria Student Law Review, 2021)
Although the Constitution of the Republic of South Africa, 1996 guarantees everyone the right of access to courts and civil justice, many people still find themselves in a position where they cannot access the South African justice system, specifically concerning civil legal matters. While this problem has been recognised by various academics, authors, and even Constitutional Court judges, the understanding of what this right means empirically has only recently been understood in relation to South Africa’s civil justice system. This article, therefore, concentrates on the accessibility and effectiveness of South African civil courts. The focus is on civil lower courts given that most people who are exposed to the civil justice system do so by means of the Magistrates Courts only.